Effects of Recombinant Human Erythropoietin on Resistance Artery Endothelial Function in Stage 4 Chronic Kidney Disease: Role of Oxidative Stress and Endothelin‐1. Issue 2 (12th April 2013) - Briet, Marie; Barhoumi, Tlili; Mian, Muhammad Oneeb Rehman; Sierra, Cristina; Boutouyrie, Pierre; Davidman, Michael; Bercovitch, David; Nessim, Sharon J.; Frisch, Gershon; Paradis, Pierre; Lipman, Mark L.; Schiffrin, Ernesto L.
Abstract : Background: Recent studies have raised concern about the safety of erythropoiesis‐stimulating agents because of evidence of increased risk of hypertension and cardiovascular morbidity and mortality in chronic kidney disease (CKD) patients. In the present study, we investigated the effects of recombinant human erythropoietin (EPO) on endothelial function of gluteal subcutaneous resistance arteries isolated from 17 stage 4 patients (estimated glomerular filtration rate 21.9±7.4 mL/min per 1.73 m 2 ) aged 63±13 years. Methods and Results: Arteries were mounted on a pressurized myograph. EPO impaired endothelium‐dependent relaxation in a concentration‐dependent manner. The maximal response to acetylcholine with EPO at 1, 10, and 20 IU/mL was reduced by 12%, 34%, and 43%, respectively, compared with the absence of EPO ( P <0.001). EPO‐induced endothelial dysfunction was significantly associated with carotid stiffness and history of cardiovascular events. EPO had no effect on norepinephrine‐induced vasoconstriction or sodium nitroprusside–induced relaxation. ABT‐627, an endothelin type A receptor antagonist, and tempol, a superoxide dismutase mimetic, partially reversed the altered endothelial function in the presence of EPO ( P <0.01). Increased expression of endothelin‐1 was found in the vessel wall after incubation with EPO. Conclusions: EPO alters endothelial function of resistance arteries in CKD patients via a mechanism involving in part oxidative stress and signaling through an endothelin type A receptor. EPO‐induced endothelial dysfunction could contribute to deleterious effects of EPO described in large interventional trials.